Effect of hemoglobin levels and upper arm circumference of pregnant on stunting in toddlers - Iin Setiawati; Maulana, Tiya (MEDIA ILMU KESEHATAN, 2024)
Background:The highest proportion of stunting is found in East Nusa Tenggara and West Nusa Tenggara. In December 2018 the average stunting case in NTB reached 37.2% (around 150,000 children). At the Pabelilo Health Center in 2021 the most cases of stunting were in Panda Village, there was an increase of 4.8%, from 23 toddlers (9.8%) to 44 toddlers (14.6%) in 2022Objective:Analyzing effect of hemoglobin levels and upper arm circumference of pregnant on incidence of stunting in toddlersMethods:The research method uses analytic with a cross-sectional approach. Sample of 124 toddlers, simple random sampling technique, Palibelo Bima Public Health Center from February to March 2023. Ethical certificate 1573/KEPK/STIKES-NHM/EC/II/2023. Statistical test using multiple linear regression ? 0.05Results: Hemoglobin levels of pregnant in toddlers who experience stunting are almost halved, 9.5-10.5 grams/dl, namely 17 toddlers (38.6%). The upper arm circumference in toddlers who experience stunting is almost entirely 19.5-22.5 cm in 35 toddlers (79.6%). Statistical tests show ?<? (0.00<0.05), which means that hemoglobin levels and upper arm circumference simultaneously have a significant effect on stunting in toddlersConclusion: Hemoglobin levels and upper arm circumference of pregnant have an effect on the incidence of stunting in toddlers, but partially the hemoglobin level of pregnant has no effect on the incidence of stunting in toddlers while the circumference of the upper arms has an effect on the incidence of stunting in toddlers